A simple nonparametric car-following model driven by field data. (October 2015) - He, Zhengbing; Zheng, Liang; Guan, Wei
Highlights: A nonparametric car-following model based on k -nearest neighbour is proposed. Neither mathematical equation nor calibration is needed in the model. Neither fundamental diagrams nor driver's behaviour parameters is assumed. The model is simple and parsimonious, because there is only one parameter. The model is able to well reproduce important traffic characteristics. Abstract: Car-following models are always of great interest of traffic engineers and researchers. In the age of mass data, this paper proposes a nonparametric car-following model driven by field data. Different from most of the existing car-following models, neither driver's behaviour parameters nor fundamental diagrams are assumed in the data-driven model. The model is proposed based on the simple k -nearest neighbour, which outputs the average of the most similar cases, i.e., the most likely driving behaviour under the current circumstance. The inputs and outputs are selected, and the determination of the only parameter k is introduced. Three simulation scenarios are conducted to test the model. The first scenario is to simulate platoons following real leaders, where traffic waves with constant speed and the detailed trajectories are observed to be consistent with the empirical data. Driver's rubbernecking behaviour and driving errors are simulated in the second and third scenarios, respectively. The time–space diagrams of the simulated trajectories are presented and explicitly analysed. It is demonstrated that the model is able to well replicate periodic traffic oscillations from the precursor stage to the decay stage. Without making any assumption, the fundamental diagrams for the simulated scenario coincide with the empirical fundamental diagrams. These all validate that the model can well reproduce the traffic characteristics contained by the field data. The nonparametric car-following model exhibits traffic dynamics in a simple and parsimonious manner.